A Survey on Sufficient Conditions for Hamiltonian Cycles in Bipartite Digraphs - Ge, Huifen; Zhang, Shumin; Ye, Chengfu (Discontinuity, Nonlinearity, and Complexity, 2026)
A digraph $D=(V,A)$ is called a bipartite digraph if there exists a partition $(X,Y)$ of $V(D)$ into two partite sets such that every arc of $D$ has its end-vertices in different partite sets. It is called balanced if $|X| = |Y|$. If a digraph $D$ has a directed cycle $C$ which covers all of its vertices, then $D$ is Hamiltonian. This paper mainly introduces some sufficient conditions for Hamiltonian cycles in balanced bipartite digraph.